2022
DOI: 10.3389/fnint.2022.818692
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effect of Preventive Supplementation of Omega-3 Fatty Acid in a Complex Regional Pain Syndrome Type I Model in Mice

Abstract: ObjectiveComplex regional pain syndrome (CRPS) is usually triggered by trauma or a surgical procedure, and it typically becomes an established one after an intense inflammatory process with chronic pain and edema as the main symptoms. Available treatments for CRPS have low efficacy. This study aimed to evaluate the clinical and immunoregulatory effects of omega-3 polyunsaturated fatty acid (PUFA) supplementation on paw edema and anti- and pro-inflammatory cytokines and macrophage phenotypes in the chronic post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Studies have found that n-3 PUFAs can participate in regulating the production and secretion of cytokines and chemokines in macrophages, thus having the phagocytic ability of macrophages ( 20 ). In addition, some studies have also pointed out that n-3 PUFAs could change the activation state of macrophages ( 21 23 ). In the course of research, n-3 PUFAs are found to play an important role in neutrophils, which is related to the n-3/n-6 competition.…”
Section: The Protective Function Of N-3 Pufasmentioning
confidence: 99%
“…Studies have found that n-3 PUFAs can participate in regulating the production and secretion of cytokines and chemokines in macrophages, thus having the phagocytic ability of macrophages ( 20 ). In addition, some studies have also pointed out that n-3 PUFAs could change the activation state of macrophages ( 21 23 ). In the course of research, n-3 PUFAs are found to play an important role in neutrophils, which is related to the n-3/n-6 competition.…”
Section: The Protective Function Of N-3 Pufasmentioning
confidence: 99%